The effects of Klotho delivering mesenchymal stem cell-derived small extracellular vesicles on acute kidney injury - Xiao-Hui Deng; Zi-Cong Wu; Qi Sun; Long-Xin Huang; Ying-Chun Xie; Dong-Xiao Lou; Chan-Gu Li; Xiao-Qing Liu; Zhi-Rou Zhou; Tian Tian; Chang-Lin Lian; Qing-Ling Fu (Journal of Nanobiotechnology)
Abstract Acute kidney injury (AKI) is a life-threating syndrome characterized by sudden loss of kidney function, and its management is challenging and often suboptimal. Mesenchymal stem cells (MSCs) have shown promise in AKI therapy in pre-clinical and clinical trials; however, their clinical application still faces many challenges. MSC-derived small extracellular vesicles (sEV) may help overcome these challenges. In the current study, we overexpressed Klotho in MSCs and then isolated Klotho-loaded sEV (Klotho-sEV) using anion-exchange chromatography. Klotho-sEV displayed characteristics comparable to those of sEV in terms of size, morphology, conventional markers, and biosafety, as well as a higher abundance of Klotho protein. In rhabdomyolysis-induced AKI, sEV showed preferential tropism in injured kidneys. We found significantly and stably accelerated renal recovery, mitigated functional and histological abnormalities, stimulated tubular cell proliferation, reduced injury and inflammatory marker expression, and restored endogenous Klotho loss in mice after the administration of Klotho-sEV. In addition, Klotho-sEV treatment activated the mTOR and MEK1/2 signaling pathways. Proteomics and small RNA sequencing analyses of sEV and Klotho-sEV revealed abundant proteins and miRNAs involved in anti-inflammation and reno-protection, and Klotho-sEV showed characteristics that were different from those of sEV. In conclusion, Klotho-sEV may be a promising cell-free strategy for the treatment of AKI. Graphical abstract